The Effect Of Culturing The Value Of Tauhid On Maturity Attitudes Of Children (Case Study Of The Salafi Community In Pondok Aren Tangerang Selatan) - Muhamad Fajri (Universitas PGRI Yogyakarta, 2023)
This research aims to find out whether there is an effect on the instilling of tawhid values on the maturity of children's attitudes in Salafi community of Pondok Aren South Tangerang, as well as analyze how much the effect is. This type of research was correlational by analyzing data in the form of descriptive statistics and simple regression. The population in this study was children aged 4 to 7 years and children aged 8 to 12 years in Salafi community in Pondok Aren South Tangerang. This study used purposive sampling as much as 20% of the total population of approximately 200 children. Meanwhile, the method of data collection used was with questionnaire. From the results of the calculation, the effect of instilling tawhid value got different (R square). Instilling the value of tawhid in children aged 4 to 7 years had an influence (R Square) of 0.588 or 58.8% towards the maturity of the children's attitude. Meanwhile, the instilling of tawhid value in children aged 8 to 12 years had an effect (R Square) of 0.654 or 65.4% on the maturity of the children's attitude. Meanwhile, the overall instilling of tawhid value in children had an influence (R Square) of 0.585 or 58.5% on the maturity of the children's attitude. The rest were other factors that were not studied by researcher.